6-Hydroxydopamine induces secretion of PARK7/DJ-1 via autophagy-based unconventional secretory pathway. Issue 11 (2nd November 2018) - Urano, Yasuomi; Mori, Chinatsu; Fuji, Ayano; Konno, Keito; Yamamoto, Takayuki; Yashirogi, Shohei; Ando, Mayu; Saito, Yoshiro; Noguchi, Noriko
ABSTRACT: PARK7/DJ-1 is a Parkinson disease- and cancer-associated protein that functions as a multifunctional protein involved in gene transcription regulation and anti-oxidative defense. Although PARK7 lacks the secretory signal sequence, it is secreted and plays important physiological and pathophysiological roles. Whereas secretory proteins that lack the endoplasmic reticulum-targeting signal sequence are secreted from cells by way of what is called the unconventional secretion mechanism, the specific processes responsible for causing PARK7 to be secreted across the plasma membrane have remained unclear. In the present study, we found that PARK7 secretion was increased by treatment with 6-OHDA via the unconventional secretory pathway in human neuroblastoma SH-SY5Y cells and MEF cells. We also found that 6-OHDA-induced PARK7 secretion was suppressed in Atg5-, Atg9 -, or Atg16l1 -deficient MEF cells or ATG16L1 knockdown SH-SY5Y cells, indicating that the autophagy-based unconventional secretory pathway is involved in PARK7 secretion. We moreover observed that 6-OHDA-derived electrophilic quinone induced oxidative stress as indicated by a decrease in glutathione levels, and that this was suppressed by pretreatment with antioxidant NAC. We further found that NAC treatment suppressed autophagy and PARK7 secretion. We also observed that 6-OHDA-induced autophagy was associated with activation of AMPK and ULK1 via a pathway which was independent of MTOR. Collectively these results suggest that electrophilic 6-OHDA quinone enhances oxidative stress, and that this is followed by AMPK-ULK1 pathway activation and induction of secretory autophagy to produce unconventional secretion of PARK7. Abbreviations: 6-OHDA: 6-hydroxydopamine; AMPK: AMP-activated protein kinase; ATG: autophagy related; CAV1: caveolin 1; ER: endoplasmic reticulum; FN1: fibronectin 1; GSH: glutathione; IDE: insulin degrading enzyme; IL: interleukin; LDH: lactate dehydrogenase; MAP1LC3B/LC3B: microtubule associated protein 1 light chain 3 beta; MEF: mouse embryonic fibroblast; MTOR: mechanistic target of rapamycin kinase; NAC: N-acetyl-L-cysteine; PARK7/DJ-1: Parkinsonism associated deglycase; PD: Parkinson disease; RPS6KB1/p70S6K: ribosomal protein S6 kinase B1; RPN1: ribophorin I; ROS: reactive oxygen species; ULK1: unc-51 like autophagy activating kinase 1; WT: wild-type